Membrane-induced folding of cecropin A. - Silvestro, L (2000)
Lipid membranes manifest a diverse array of surface forces that can fold and orient an approaching protein. To better understand these forces and their ability to influence protein function, we have used infrared spectroscopy with isotopic editing to characterize the 37-residue membrane-active antimicrobial polypeptide cecropin A as it approached, adsorbed onto, and finally penetrated various lipid membranes. Intermediate stages in this process were isolated for study by the use of internal reflection and Langmuir trough techniques. Results indicate that this peptide adopts well-ordered secondary structure while superficially adsorbed to a membrane surface. Its conformation is predominantly alpha-helical, although some beta structure is likely to be present. The longitudinal axis of the helical structure, and the transverse axes of any beta structure, are preferentially oriented parallel to the membrane surface. The peptide expands the membrane against pressure when it penetrates the membrane surface, but its structure and orientation do not change. These observations indicate that interactions between the peptide and deeper hydrophobic regions of the membrane provide energy to perform thermodynamic work, but separate and distinct interactions between the peptide and superficial components of the membrane are responsible for peptide folding. These results have broad implications for our understanding of the mechanism of action and the specificity of these antimicrobial peptides.